Management of Character Education in Increasing Graduates is Noble - Eka Fingkirani; Sutaryat Trisnamansyah; Uman Suherman; Sofyan Sauri (Journal of Islamicate Studies, 2020)
Character education is indeed not a new thing in the world of education, but the facts that show character education have not been in line with changes in the behavior of students. To produce noble graduates need education systems and school management which lead to the process of forming the character of students in both planning, implementation, effective evaluation. The general purpose of this study is to find out and analyze character education management in increasing noble graduates. The specific objectives of this study are analyzing and describing (1) character education planning in increasing noble achievements; (2) Implementation of character education in increasing graduates of noble character; (3) Evaluation of character education in increasing graduates of noble character; (4) The obstacles that occur in the implementation of character education in increasing noble-character graduates; (5) Character education solutions in increasing noble achievement; (6) Impact of character education management in improving noble-character graduates. The study was conducted with a descriptive study approach at SDN 1 Wanaraja Garut, SDN 1 Tegalpanjang Garut, and SDN 1 Citangtu Garut with qualitative methods. The conclusion of this study is a demand for the importance of implementing character education at all levels of education, especially in basic education, is a necessity. The condition of socio-cultural life today indicates the importance of developing character values in each individual as early as possible. Characters turned out to have an impact on changing attitudes, mindset and also the pattern of students in their daily life, so students not only become human knowledge but also have an honest, polite, polite, skilled, disciplined, and confident attitude.